S88 A human model of lung fibrosis for the assessment of anti-fibrotic strategies in idiopathic pulmonary fibrosis. (12th November 2019) - Roach, KM; Tongue, P; Castells, E; Elliot, G; Marshall, H; Richardson, M; Mason, S; Chachi, L; Bradding, P
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a progressive and invariably lethal interstitial lung disease. Animal models help with understanding disease mechanisms, but to-date, the bleomycin mouse model of lung fibrosis has failed to predict drug efficacy. We have developed a human model of lung fibrosis that provides a more physiological representation for the assessment of anti-fibrotic strategies in IPF. Pirfenidone and nintedanib are currently approved for the treatment of IPF but have limited efficacy and their mechanisms of action are poorly understood. In this study we have compared the anti-fibrotic effects of pirfenidone, nintedanib and a potential novel therapy, senicapoc (KCa 3.1 channel inhibitor) in our human model. Methods: 2 mm 3 pieces of human lung parenchyma were cultured for 7 days in DMEM ± TGFβ1 (10 ng/ml) ± pirfenidone (500 µM), nintedanib (1 µM), senicapoc (100nM). Pro-fibrotic pathways were examined by RT-PCR and soluble collagen secretion. Results: In 45 donor lung samples tested, 44 out of 84 IPF- and fibrosis-associated genes tested were significantly upregulated by TGFβ1. Nintedanib (n=13) and pirfenidone (n=11) dysregulated the mRNA expression of 14 and 2 fibrosis-associated genes respectively. Nintedanib attenuated the TGFβ1-dependent upregulation of mRNA for numerous MMPs, Integrin's and PDGF, but upregulated α-SMA. Pirfenidone attenuated the TGFβ1-dependent expression of MMP3 and 13, but did not upregulate the expression of any genes. In comparison, senicapoc (n=11) attenuated TGFβ1-dependent upregulation of 28 fibrosis-associated genes, including α-SMA, PDGF, collagen type III, ITGAV and ITGB6. Conclusions: This human experimental model of lung fibrosis recapitulates pro-fibrotic events evident in IPF and shows sensitivity to pirfenidone and nintedanib inhibition. Pirfenidone and nintedanib impact different molecular pathways. Senicapoc inhibited significantly more fibrosis-associated genes than pirfenidone and nintedanib, supporting the view that KCa 3.1 channels are a promising target for the treatment of IPF